Bilateral Choroidal Metastasis from Non-Small Cell Lung Cancer - Tariq Namad; Jiang Wang; Annemarie Tilton; Nagla Abdel Karim (Case Reports in Oncological Medicine)
Breast and lung cancers are the most common primary neoplasms to manifest with choroidal metastases. The incidence of choroidal metastases from metastatic lung cancer was reported to be 2–6.7%. We report a case of bilateral choroidal metastasis from non-small cell lung cancer. A 59-year-old Caucasian female patient, never a smoker, was diagnosed with stage IV lung adenocarcinoma metastatic to the pleura, bones, and the brain. Her initial scan of the chest showed innumerable soft tissue nodules and mediastinal adenopathy compatible with metastatic disease. Her initial brain MRI showed numerous small enhancing lesions consistent with extensive disease. Unfortunately, during her follow-up visits, she presented with bulge on her left eye. Simultaneously, her follow-up chest scan showed increase in the size of the lung nodules. She continued to have a reasonable performance status at that time, except for mild increase in her dyspnea. The choroidal metastases require a multidisciplinary care and should be among the differential patients with malignancy who present with ocular symptoms.